2017
DOI: 10.1002/ange.201710301
|View full text |Cite
|
Sign up to set email alerts
|

CO Hydrogenation on Cobalt‐Based Catalysts: Tin Poisoning Unravels CO in Hollow Sites as a Main Surface Intermediate

Abstract: Site poisoning is a powerful method to unravel the nature of active sites or reaction intermediates. The nature of the intermediates involved in the hydrogenation of CO was unraveled by poisoning alumina‐supported cobalt catalysts with various concentrations of tin. The rate of formation of the main reaction products (methane and propylene) was found to be proportional to the concentration of multi‐bonded CO, likely located in hollow sites. The specific rate of decomposition of these species was sufficient to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…However, the selectivity monotonically dropped as the In composition increased (37% for Fe20In, 23% for Fe10In, and 20% for Fe20In3), which suggested that the unselective dehydrogenation and C−C/CC bond cleavage reaction paths could be limited by incorporating the In element into the Fe catalyst. Our observations were supported by the study of the Snpromoted Co catalyst in FTS by Meunier and co-workers, where the CH 4 selectivity was systematically inhibited by improving the concentration of the Sn element into Co. 26 Figure 3b shows the correlation between the selectivity of C2−C4 hydrocarbons (total and olefins) and the In composition in the catalysts. A volcano type of trend was found with Fe10In exhibiting the highest selectivity toward both total hydrocarbons and olefins.…”
Section: ■ Results and Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…However, the selectivity monotonically dropped as the In composition increased (37% for Fe20In, 23% for Fe10In, and 20% for Fe20In3), which suggested that the unselective dehydrogenation and C−C/CC bond cleavage reaction paths could be limited by incorporating the In element into the Fe catalyst. Our observations were supported by the study of the Snpromoted Co catalyst in FTS by Meunier and co-workers, where the CH 4 selectivity was systematically inhibited by improving the concentration of the Sn element into Co. 26 Figure 3b shows the correlation between the selectivity of C2−C4 hydrocarbons (total and olefins) and the In composition in the catalysts. A volcano type of trend was found with Fe10In exhibiting the highest selectivity toward both total hydrocarbons and olefins.…”
Section: ■ Results and Discussionsupporting
confidence: 75%
“…This ability appeared to be reduced when In was introduced, which could be attributed to the blocking of the surface reaction sites or an interaction between Fe and In. A similar phenomenon was also observed in the published work on Pd + In, Pt + Sn, Ni + Ga, and Co + Sn catalysts, where the amount of surface metal sites and the surface reactivity were systematically reduced as the loading of promoters increased. ,, Turnover frequency rates for the catalysts were also determined using an in situ CO TPD study to estimate the number of surface reaction sites for overall rate normalization. They were calculated to be 6.49 × 10 –2 , 2.22 × 10 –1 , 8.48 × 10 –2 , and 7.21 × 10 –2 s –1 for Fe, Fe20In, Fe10In, and Fe20In3, respectively.…”
Section: Results and Discussionsupporting
confidence: 58%
See 3 more Smart Citations